Mutual coupling reduction in array elements using EBG structures - Sajjad, Hassan; Khan, Sana; Arvas, Ercüment (Institute of Electrical and Electronics Engineers, 2017)
A 2D electromagnetic band gap (EBG) structure is designed on the ground plane of 1×2 rectangular patch antenna array to reduce the mutual coupling between the two elements and enhance the radiation pattern. An isolation of -41 dB has been achieved with the EBG structure relative to -20 dB without the EBG.
Keywords: Electromagnetic Band Gap; Mutual Coupling; Patch Antenna Array